2023
DOI: 10.1002/cctc.202300349
|View full text |Cite
|
Sign up to set email alerts
|

Bending the ORR Scaling Relations on Zirconium Oxynitride for Enhanced Oxygen Electrocatalysis

Abstract: Technologies like polymer electrolyte membrane fuel cells play an important role in environmentally friendly energy conversion. Essential for their commercialization is the development of cheap and efficient electrocatalyst for the oxygen reduction reaction (ORR). Non-platinum group metal (PGM) based catalysts has exhibited favourable activity in acidic electrolytes. In this study, we computationally explore the catalytic sites on the (111) surface of hydrated zirconium oxynitride using periodic DFT calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
(104 reference statements)
0
0
0
Order By: Relevance
“…[30] In our previous work we have explored the possibility of enhanced ORR activity due to bending of ORR scaling relations. [31] We concluded that the G O -G OH scaling relation for ORR on Zr 2 ON 2 catalyst indeed shows deviation from the standard scaling relation, however, there was no indication that it necessarily results in enhanced electrocatalysis. Several electronic descriptors failed to capture the complexity of the Zr 2 ON 2 catalyst surface that arises from presence of two different anions i. e. oxygen and nitrogen in the anionic layers.…”
Section: Introductionmentioning
confidence: 78%
“…[30] In our previous work we have explored the possibility of enhanced ORR activity due to bending of ORR scaling relations. [31] We concluded that the G O -G OH scaling relation for ORR on Zr 2 ON 2 catalyst indeed shows deviation from the standard scaling relation, however, there was no indication that it necessarily results in enhanced electrocatalysis. Several electronic descriptors failed to capture the complexity of the Zr 2 ON 2 catalyst surface that arises from presence of two different anions i. e. oxygen and nitrogen in the anionic layers.…”
Section: Introductionmentioning
confidence: 78%